The effect of inter-letter spacing on reading performance and eye movements in typically reading and dyslexic children. (August 2022) - Łuniewska, Magdalena; Wójcik, Marta; Jednoróg, Katarzyna
Abstract: Recent studies have suggested that an increase of inter-letter spacing may improve reading performance of dyslexic readers by reducing visual crowding. However, these results have been difficult to replicate. This study directly compares reading accuracy and comprehension, as well as reading speed, and number and duration of fixations of 38 dyslexic and 32 typically reading children (10–14 years old) in regular, spaced (+2, 5 pt), and condensed (−1, 5 pt) conditions using a natural sentence-reading paradigm. Inter-letter spacing did not affect reading accuracy, comprehension, or speed. The lack of effects of inter-letter spacing was observed in both dyslexic and typical readers. Inter-letter spacing did not impact the number of fixations, but increased inter-letter spacing led to shorter fixations in dyslexic children. Decreased inter-letter spacing resulted in longer fixations in both groups. These results do not support the claim that dyslexics are more influenced by crowding than age-matched controls. Highlights: Increased inter-letter spacing has no impact on reading accuracy, speed and comprehension. Neither dyslexic nor typical readers showed effects regarding inter-letter spacing. Inter-letter spacing does not affect the number of fixations. Decreased inter-letter spacing led to longer fixations in typical and dyslexic readers.